Analisis Sanitasi Lingkungan Rumah Tangga Terhadap Stunting Pada Balita - Halimah Halimah; Imam Santoso; Rahmawati Rahmawati; Erminawati Erminawati (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
Stunting is not only caused by chronic nutrition, but also infectious diseases related to environmental sanitation. The state of sanitation greatly affects the health of the occupants of the house, including the nutritional status of children. Stunting toddlers will have a lower level of intelligence and get sick more easily. The purpose of this study was to determine the relationship between household environmental sanitation with the incidence of stunting in toddlers. This research is analytic,the number of samples was 42 respondents consisting of 21 stunting toddlers and 21 normal toddlers. Statistical analysis using the Gamma correlation test, with the results showing the relationship between the variables of clean water facilities of 0.011 < α (0.05) and the relationship of family latrine variables of 0.002 < α (0.05) it can be stated that there is a relationship between clean water facilities and family latrines with stunting in toddlers. For the community, it is hoped that improvements to clean water facilities such as providing waterproof walls with a depth of 3 meters from the ground surface and family latrine facilities by closing the latrine floor that is not tight.